Economic, social and behavioral development of farmers through Farmer FIRST Programme in Punjab - Singh, Kuldeep; Kumar, Pankaj; Kalra, Vajinder Pal; Singh, Dalbeer (Indian Farming, 2022)
Farmer FIRST Programme was initiated by ICAR to uplift the farmers’ livelihood as a novel grassroot methodology. In Punjab, it was started in the Chatha Nanhera and Taranji Khera villages of Sangrur to tackle the various farming issues through natural resourcemanagement, diversification, introduction of high yielding vegetable varieties, value-addition, subsidiary  occupations and livestock-based modules. Benchmark surveys had revealed that farmers in the adopted villages indulged in resource-depleting farming practices so FFP team brainstormed and identified various technological, behavioural problems and planned interventions accordingly. For technology upscaling in the project villages, scientist from Punjab Agricultural University laid various frontline demonstrations resulted into better natural resource management, diversification and income enhancement of the farmers. The continuous farmer-scientist interface through trainings, group meeting, campaigns, field visits, and farmers’ fairs was maintained to popularize these technologies/practices among the farmers. Further, farmer-to-farmers extension model has been developed in the villages throughbehavioural training of the farmers and these opinion leaders are extending the knowledge to other large number of farmers. To summarize, it can be said that FFP worked as a path breaking programme in Sangrur (Punjab) to uplift the livelihood of farmers through its novel methodology. It enabled the farmers to think and do beyond the conventional practices and changed theperspective of farming in their minds.